Antidiabetic Activity of Clerodendron phlomoidis Leaf Extract in Alloxan-Induced Diabetic Rats - Dhanabal, S. P. (Medknow Publications, 2008)
Ethanol extract of leaves of Clerodendron phlomoidis L. subjected to preliminary qualitative phytochemical investigations showed the presence of alkaloids, phytosterols, glycosides, saponins, phenolic compounds, proteins and flavonoids. The extract was screened for hypoglycemic activity in alloxan-induced diabetic rats (120 mg/kg, i.p.) at two dose levels, viz., 100 and 200 mg/kg. The ethanol extract at 200 mg/kg dose level exhibited significant (p<0.05) hypoglycemic activity and also correction of altered biochemical parameters viz., cholesterol and triglycerides (p<0.05).